Natural dyes from amazon forest: potential application in dye-sensitized solar cells - Amâncio,Moisés do Amaral (2021)
ABSTRACT In this work, plant dyes extracted from Amazon Forest are applied as a sensitizer in Dye-Sensitized Solar Cells. The selected plants were Euterpe oleracea, Arrabidaea chica, Bixa orellana, Genipa Americana, and Myrcia sylvatica, and the dyes were collected from fruits, leaves, seeds, pulp and seeds and stalk scrapings respectively. Characterization studies by the UV-vis spectroscopy made it possible to know the absorption spectra of each plant dye, and the X-ray diffraction technique allows the structural characterization of the nanostructured semiconductor layer. The solar cells were characterized according to their efficiency parameters (Voc, Jsc, FF and ? (%)), obtained from the current vs voltage curves. Such parameters proved to be modest, presenting Voc and Jsc values over 0.334 volts and 0.452 mA/cm2 for a photosensitized cell with the dyes extracted from Genipa americana. In this way, it was possible to verify the photoelectrochemical potential of the dyes extracted from plants of the Amazon Forest.